The Impact of Financial Technology and Operational Efficiency on Banking Profitability in Indonesia 2021-2024 - Sengka, Lola Violin; Sjeddie R. Watung; Linda A. O. Tanor (Prodi Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas PGRI Madiun, 2026)
This study aims to analyze the influence of financial technology (fintech) and operational efficiency on banking profitability in Indonesia during the 2021-2024 period. Fintech is measured by the number of mobile banking transactions, operational efficiency is proxied by the BOPO ratio, and profitability is measured by ROA. The study used a quantitative method with panel data regression analysis, and the best model obtained was the Random Effects Model (REM) with the help of EViews 12. Based on the analysis results, fintech has a significant positive effect on ROA, while operational efficiency has a significant negative effect on ROA. These results indicate that improving digital services and controlling operational costs play a significant role in improving banking financial performance